FUNCTIONALITY OF PERSONS SUBMITTED TO TOTAL SHOULDER ARTHROPLASTY BY PROXIMAL HUMERUS FRACTURES: RETROSPECTIVE STUDY - Carolina Tiago Afonso; Miguel Pinto Freitas; Nuno Gonçalo Pais; Daniel Ramos Pires; André Novo; Afonso Salgado Ruano (Associação Portuguesa dos Enfermeiros de Reabilitação, 2019)
Objective: To retrospectively identify, in people submitted to total shoulder arthroplasty for proximal humeral fractures, the type of arthroplasty used, the functional shoulder scores, the recorded complications, the influence of the elapsed time from the fracture and the placement of the implant in the final functional outcome. Method: Retrospective study between 2014 and 2017. The following variables were identified: age, sex, time between fracture and surgery, type of arthroplasty, cementation, modularity, rehabilitation, complications, follow-up time and functionality. Data from the scales Constant Shoulder Score and American Shoulder and Elbow Surgeons Standardized Shoulder Assessment Form were obtained. Results: Sample comprised of 12 women and 3 men with mean age of 78 years and a mean time between fracture and surgery of 29.4 days. In terms of functionality, it was observed that persons with inverse prosthesis presented better results compared to the ones submitted to hemiarthroplasty (53.2 vs. 41.1 and 68.5 vs. 44.6). The follow-up was done during 29.4 months. Conclusion: The reverse prosthesis seems to be the best treatment option and allows better functionality. Prosthetic modularity is important.